Islamic Tourism in Indonesia Context in PISA-Like Mathematics Problem - Miranda Salim Paseban; Agustiany Dumeva Putri; Liana Septy; Harisman Nizar (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2023)
The aim of research was to producing PISA-like mathematics problem in using Islamic tourism context in Indonesia that are accordance with the PISA problem framework, had attractiveness, and had potential-effect to mathematics literacy skill on junior high school students. The subject of the research were 21 students of ninth grade A class at MTs Muhammadiyah 1 Palembang. The research method used was development research which is divided into two major stages, namely the preparation stage and the prototyping stage with Tessmer’s formative evaluation flow. The techniques of collecting data were used open questionnaire, interview, and test. The technique of analysis data was used descriptive qualitative. The final results of the study are 7 PISA-like mathematics problem in using Indonesia’s Islamic tourism context at the junior high school level that were valid based on the validator's assessment at the expert review stage. The questions had an attractiveness based on the results at the one-to-one and small group stages because it is known that students are challenged to solve problems correctly and can stimulate students thinking to use their mathematical abilities in any problems. The results of student answers at the field test stage show the potential effect that the questions developed lead to the involvement of various basic abilities and mathematical literacy in the problem solving process.Keywords: Development Research, PISA-Like Mathematics Problems, Islamic Tourism in Indonesia